Alterações metabólicas durante a superação de dormência e deterioração de sementes de amendoim forrageiro em armazenamento - Xavier, Márcia Provinzano Braga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Forage peanut seeds (Arachis pintoi Krapov. & W. C. Greg.), a widely used legume as forage in landscape and soil protection, show physiological dormancy and low longevity after harvest. Nevertheless, chemical or physical breakage of dormancy frequently accelerates seed deterioration. Successful results have been obtained upon exogenous application of ethylene. In this context, it has been investigated how dormancy breakage mediated by ethylene affects, or not, ultra-structures, physiological potential and respiratory activity of forage peanut during storage. Recently harvested seeds were divided into two groups, and one of them was treated with ethylene. Next, the seeds were submitted to moisture content assessments (wet basis), germination, seedling emergence, potassium leaching, tetrazolium, respiration and cell and mitochondria morphology, besides the quantification of hydrogen peroxide, malonaldehyde, carbohydrate, protein and amino acid. The seeds were stored in natural environment up to 26 months. Assessments were performed periodicallyThe results show that dormancy breakage can accelerate deterioration of forage peanut. However, it was observed that under uncontrolled conditions of storage environment, ultra-structural alterations of mitochondria, caused by deterioration, start long before the total dormancy breakage in the second month. Likewise, alterations in the selective permeability of membranes and effects on the seed tissues help reduce the number of normal seedlings already visible from the sixth month on. Moreover, measurable alterations of carbohydrate, amino acids, proteins, respiration and lipid peroxidation were verified from the 8th and the 10th month of storage, when seeds, mainly those treated with ethylene, lost their capacity to produce normal seedlings. Oxidative processes can determine low longevity of those seeds, and dormancy does not represent an evolutionary tool in order to enhance their storing potential.

Sementes de amendoim forrageiro (Arachis pintoi Krapov. & W. C. Greg.), leguminosa amplamente utilizada como forrageira, no paisagismo e proteção do solo, apresentam dormência fisiológica pós-colheita e baixa longevidade. Não obstante, a superação ocorre de forma natural ao longo do armazenamento e tratamentos químicos ou físicos da dormência, frequentemente, aceleram a deterioração das sementes. Resultados promissores têm sido obtidos com a aplicação exógena de etileno. Neste contexto, investigaram-se como a superação da dormência mediada pela presença de etileno, ou não, afeta as ultraestruturas, o potencial fisiológico e a atividade respiratória de sementes de amendoim forrageiro durante o armazenamento. Sementes recém-colhidas foram divididas em dois grupos, um dos quais foi tratado com ethephon. Em seguida, as sementes foram submetidas às avaliações de grau de umidade (base úmida), germinação, emergência de plântulas, lixiviação de potássio, tetrazólio, respiração e morfologia de células e mitocôndrias, além da quantificação de peróxido de hidrogênio, malonaldeido, carboidratos, proteínas e aminoácido. As sementes foram armazenadas em condições ambientais não controladas até 26 meses, com avaliações periódicas durante o armazenamento. Os resultados obtidos indicam que a superação da dormência pode acelerar a deterioração de sementes de amendoim forrageiro. No entanto, nas condições de ambiente de armazenamento empregadas, verificaram-se que alterações ultraestruturais das mitocôndrias, ocasionadas pela deterioração, se iniciam aos dois meses, muito antes da superação da dormência. Igualmente, alterações na permeabilidade seletiva das membranas e efeitos nos tecidos das sementes concorrem para a redução do número de plântulas normais, já visíveis no teste de germinação a partir do 6º mês. Mais ainda, alterações mensuráveis de carboidratos, aminoácidos...
Metabollic changes during dormancy breakage and deterioration of forage peanut seeds during storage
Keywords: Plantas forrageiras - Sementes; Sementes; Etileno; Metabolismo; Oxidação; Solos - Analise; Forage plants - Seed